The Comparison of Premature Ejaculation Assessment Questionnaires and Their Sensitivity for the Four Premature Ejaculation Syndromes: Results from the Turkish Society of Andrology Sexual Health Survey - Serefoglu, Ege C.; Yaman, Onder; Cayan, Selahittin; Asci, Ramazan; Orhan, Irfan; Usta, Mustafa F.; Kadioglu, Ates (Wiley-Blackwell, 2011)
Introduction. In addition to the previously defined lifelong and acquired premature ejaculation (PE), the existence of two more subtypes of PE, namely natural variable PE and premature-like ejaculatory dysfunction, has been proposed. Aims. To evaluate the diagnostic value of the Premature Ejaculation Diagnostic Tool (PEDT) and Arabic Index of Premature Ejaculation (AIPE) in a population-based study, in relation to their sensitivity across these four different PE syndromes and to assess the Premature Ejaculation Profile (PEP) scores of patients with lifelong, acquired, natural variable PE and premature-like ejaculatory dysfunction. Methods. Between June 2009 and December 2009, couples were randomly selected from 17 provinces of Turkey. Subjects with the complaint of ejaculating prematurely were classified as lifelong, acquired, natural variable PE, and premature-like ejaculatory dysfunction according to the medical and sexual history they described. PE status was also assessed with PEDT, AIPE and PEP. The sensitivity, specificity, positive predictive value and negative predictive value were calculated for PEDT and AIPE in the study population whereas detection rates of these two questionnaires were also compared among the four PE syndromes. Moreover, PEP scores of patients with lifelong, acquired, natural variable PE and premature-like ejaculatory dysfunction were compared. Significance level was considered as P < 0.05. Main Outcome Measures. Scores obtained from PEDT, AIPE, and PEP questionnaires. Results. A total of 2,593 couples were enrolled where 512 (20.0%) male subjects reported PE. PEDT, AIPE, and PEP measures of the PE patients indicated worse sexual function (P < 0.001 each). Mean scores obtained from questionnaires were significantly better in patients with premature-like ejaculatory dysfunction and they were the worst in patients with acquired PE (P < 0.001 each). The sensitivity values of PEDT and AIPE were 89.3 and 89.5, whereas their specificity values were 50.5 and 39.1, respectively. There were statistically significant differences in detection rates of PEDT and AIPE among the four PE syndromes (P = 0.006 and P < 0.001). They were higher in acquired and lifelong PE and lower in premature-like ejaculatory dysfunction. Conclusion. PEDT and AIPE can diagnose PE with high sensitivity, especially in patients with lifelong and acquired PE. The complaint of patients with acquired PE seems to be more severe than those complaining of lifelong, natural variable PE and premature-like ejaculatory dysfunction patients. Serefoglu EC, Yaman O, Cayan S, Asci R, Orhan I, Usta MF, Ekmekcioglu O, Kendirci M, Semerci B, and Kadioglu A. The comparison of premature ejaculation assessment questionnaires and their sensitivity for the four premature ejaculation syndromes: Results from the Turkish Society of Andrology Sexual Health Survey. J Sex Med 2011;8:1177-1185.
Keywords: Acquired Premature Ejaculation; Diagnosis; Epidemiology; Lifelong Premature Ejaculation; Natural Variable Premature Ejaculation; Patient Reported Outcomes; Premature Ejaculation; Premature Ejaculation Syndromes; Premature-Like Ejaculatory Dysfunction; Questionnaires; Sexual Dysfunction